NEUTRAL PH AND COLD TEMPERATURES STABILIZE THE PROTECTIVE EFFECT OF CRUDE PILI S. FLEXNERI ON THE ILEAL MUCOSA OF MICE - Avin Ainur Fitrianingsih; Lailia Nur Rachma; Alvi Milliana (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2019)
Alternative therapies are being sought as a result of the rising concerns with inadequate and untrustworthy medical treatments for Shigella flexneri. The current study aimed to assess the preventive and therapeutic effects of crude pili S. flexneri on of neutral pH and cold temperature against Shigella flexneri infection in immunocompetent mice. Twenty male Swiss albino mice were randomly assigned to one of two groups: control or experimental groups. Each group was subsequently separated into four equal subgroups. In order to infect the mice, 4 weeks before infection, the experimental subgroups were given crude pili S. flexneri orally in every week (three times) until the completion of the research. After following the treatment of crude pili S. flexneri, all group infected with Shigella flexneri. The small intestines of mice were processed and analyzed for the presence of the pathological lesions. Jejunal portions were measured. The findings revealed that vaccinated mice had a statistically significant increase in the quantity of health mucose as compared to non-infected group in ileal sections. Crude pili S. flexneri was administered to the intestinal portions of all subgroups before or after the infection, and the architecture was found to be more or less normal. Our data indicate that crude pili S. flexneri in neutral pH and cold temperature is a useful preventative and a potentially effective treatment medication for S. flexneri infection.